2011
DOI: 10.1186/1471-244x-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns associated with Duloxetine and Venlafaxine use for Major Depressive Disorder

Abstract: BackgroundDuloxetine and venlafaxine extended release (venlafaxine XR) are SNRIs indicated for the treatment of MDD. This study addresses whether duloxetine and venlafaxine XR are interchangeable in their patterns of use with patients who are depressed or are used more selectively based on treatment history, background characteristics, and presenting symptoms.MethodsThis was a retrospective analysis of an administrative insurance claims database. We studied patients in managed care with major depressive disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Presently, VEN is often used as an alternative drug in the treatment of selective serotonin reuptake inhibitors (SSRIs)-resistant depression being, therefore, one of the antidepressant agents most commonly prescribed worldwide [9,[12][13][14][15]. In truth, although several meta-analyses and reviews suggest that SNRIs and, in particular VEN, may be even more efficacious than SSRIs in the remission of depressive symptoms [16][17][18][19][20] and in the attainment of higher remission rates [20][21][22], not all studies support this conclusion [14,23,24]. However, VEN has been considered as a good choice for nonremitting patients [25,26].…”
mentioning
confidence: 94%
“…Presently, VEN is often used as an alternative drug in the treatment of selective serotonin reuptake inhibitors (SSRIs)-resistant depression being, therefore, one of the antidepressant agents most commonly prescribed worldwide [9,[12][13][14][15]. In truth, although several meta-analyses and reviews suggest that SNRIs and, in particular VEN, may be even more efficacious than SSRIs in the remission of depressive symptoms [16][17][18][19][20] and in the attainment of higher remission rates [20][21][22], not all studies support this conclusion [14,23,24]. However, VEN has been considered as a good choice for nonremitting patients [25,26].…”
mentioning
confidence: 94%
“…Sertraline has safe pharmacokinetics in patients with ESRD, and treatment with sertraline in PD patients is associated with improved of QoL and fewer symptoms of depression (Atalay et al, 2010). Duloxetine and venlafaxine, which are categorized as serotonin-norepinephrine reuptake inhibitors, are beneficial for patients with major depressive disorder (Ye et al, 2011). However, these agents' safety and efficacy have not been specifically established for HD patients.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Using usual care data, Ye et al . () found that patients with more comorbidities and higher prior health care costs were preferentially prescribed DLX relative to VLX. Liu et al .…”
Section: Discussionmentioning
confidence: 94%
“…Prior use (one year period) of medications included specified therapeutic classes as well as selected individual drugs known to be used in treating depression, psychosis, bipolar disorders, anxiety, sleep disorders, or chronic pain or known to be associated with initiation of DLX (Kroenke et al ., ; Liu et al ., ; Stafford et al ., ; Ye et al . ).…”
Section: Methodsmentioning
confidence: 99%